2002
DOI: 10.1016/s0012-365x(01)00325-9
|View full text |Cite
|
Sign up to set email alerts
|

On some intriguing problems in hamiltonian graph theory—a survey

Abstract: We survey results and open problems in hamiltonian graph theory centered around three themes: regular graphs, t-tough graphs, and claw-free graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Many such results involve degree conditions and other neighborhood conditions. Such results have been surveyed in several papers (see, e.g., [12,23,28]). We do not want to discuss such conditions in this survey, but here is a connectivity-only result.…”
Section: Related Results With Additional Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many such results involve degree conditions and other neighborhood conditions. Such results have been surveyed in several papers (see, e.g., [12,23,28]). We do not want to discuss such conditions in this survey, but here is a connectivity-only result.…”
Section: Related Results With Additional Conditionsmentioning
confidence: 99%
“…Although the 2-tough conjecture restricted to claw-free graphs is equivalent to Conjecture 1, it is beyond the scope of this survey. We refer the reader to [12] for more details. Inspired by these techniques, independently of [39] it has been shown in [14] that Conjectures 1 and 2 are equivalent to seemingly weaker conjectures in which the conclusion is replaced by a conclusion similar to the one in Conjecture 16.…”
Section: Conjecture 16mentioning
confidence: 99%
“…For more detailed information we refer to an excellent survey by Broersma [76], where the author gives a description of a very useful proof technique based on a variation of Woodall's hopping lemma [281].…”
Section: Chvátal-erdős Theoremmentioning
confidence: 99%
“…It is worth noting that Bauer et al [29] showed that the problem of recognizing tough graphs is NP-hard. For surveys joining hamiltonian properties and toughness we recommend the articles by Bauer, Schmeichel and Veldman [34], Bauer, Broersma and Schmeichel [22,24] and Broersma [76].…”
Section: Chvátal-erdős Theoremmentioning
confidence: 99%
See 1 more Smart Citation